Making the Sustainable University Trials and Tribulations - Leone, Katie; Komisar, Simeon; Everham III, Edwin M.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2021)
This book documents strategies for universities engaging sustainability challenges through the education of global citizens on topics such as climate change, habitat alteration, species loss, resource depletion and contamination, food access and sovereignty, economic equity, and energy use. Different disciplines and operational units often have disparate ideas in mind when they work toward advancing sustainability. For example, some disciplines focus on environmental challenges (identifying impacts to ecosystems, mitigation and remediation strategies), some on greening of industrial and commercial practices while others address social equity$1 (Boften there is little effort to connect these pieces especially while considering economic impacts. This book examines how Florida Gulf Coast University has attempted to infuse sustainability across curricula and operations as an integrated concept and our successes and shortcomings are instructional for sustainability practitioners on college campuses and other industries in a wide audience.s
Chapter 1 The Sustainability Perspective at Florida Gulf Coast University -- Chapter 2 Our Creation Story -- Chapter 3 Planning the Sustainable University: From Aspiration to Implementation -- Chapter 4 Creating a Culture of Sustainability: Organizational Strategies and Employee Training -- Chapter 5 University Colloquium: Educating for a Sustainable Future -- Chapter 6 Infusing Sustainability Across the Curriculum -- Chapter 7 Grounded in Place: Strategies for Teaching Sustainability in Cross-Cultural Learning Communities -- Chapter 8 Campus as a Living laboratory: the Built Environment -- Chapter 9 Campus as a Living Laboratory: Conservation Areas that Create a Community who Then Ensure its Sustainability -- Chapter 10 Implementing Sustainability: How Partnerships in Higher Education Operationalize Sustainability Lessons Taught in the Classroom -- Chapter 11 Service-Learning as a High Impact Practice -- Chapter 12 Student Leadership and Sustainability: The Florida Gulf Coast University Food Forest and the Real Food Challenge Pledge -- Chapter 13 Students in the Driver$1 (Bs Seat -- Chapter 14 Mission-driven Education and Research in Action: Center for Environmental and Sustainability Education -- Chapter 15 The FGCU Effect: Institutional Impact on Regional Sustainability -- Chapter 16 Assessing Sustainability: Measuring Individual and Institutional Progress -- Chapter 17 Building a green and sustainable university: An international review -- Chapter 18 Leaders and Heroes: Sustaining the Sustainable University -- Afterword: Sustainability in the time of Covid-19.s
Keywords: Environmental education; Education, Higher; Sustainability; Environmental and Sustainability Education; Higher Education; Sustainability